Needs Analysis for Developing PjBL-STEM-Based E-Modules on the Circulatory System to Enhance Critical Thinking Skills - Nuriel Hudawati; Baskoro Adi Prayitno; Meti Indrowati (Universitas Sebelas Maret, 2025)
Critical thinking has become an intrinsic part of our lives in educational as well a professional field while moving to 21st alongside, it is essential for progression. While integration of more advanced material into secondary education may be one step in right direction, schools must also need to better prepare their students for the diverse social lives and increasingly competitive economic landscapes—and workplaces that inherently require higher degreeing-of than before. The PjBL (Project-Based Learning) model combined with STEM provides students real and relevant science concept-building layered on technology, engineering, mathematics skill development. Based on the above background, e-module development steps need to begin with needs assessment for teachers and students in PjBL-STEM. This study describes the results of a needs analysis for PjBL-STEM e-module development. This research subjects are 11th-grade of biology teacher and students at the government high school where comprise SMAN 1 Dagangan. This descriptive research using questionnaires and instruments are created based on aspects of critical thinking skills. The result of the study found that (1) learning still has not used e-module, and (2) needs to be developed PjBL-STEM-based e-modules to improve students' critical thinking skills.